Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1074/jbc.272.11.7253
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Formation and Macrophage Resistance to Nitric Oxide-mediated Apoptosis

Abstract: RAW 264.7 macrophages, when challenged with a combination of lipopolysaccharide (10 g/ml) and interferon-␥ (100 units/ml), respond with endogenous NO ⅐ formation, which ultimately results in apoptotic cell death. Apoptosis is detected morphologically by chromatin condensation. Concomitantly we noticed the accumulation of the tumor suppressor protein p53. NO ⅐ -derived apoptosis was blocked by the NO ⅐ -synthase inhibitor N Gmonomethyl-L-arginine. Repetitive treatment of RAW 264.7 macrophages with lipopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 36 publications
(42 reference statements)
3
83
0
1
Order By: Relevance
“…It has been demonstrated that, whereas murine-and bovine-stimulated macrophages can produce copious amounts of NO, human, caprine, lapine and porcine cells may not be able to do so. 19,20 Thus, although it is clear that stimulation of murine macrophages with LPS and IFN-g provokes NO production from iNOS, which is sufficient to induce apoptosis, [21][22][23][24] it is by no means certain that this is also the case in human cells. Nevertheless, despite the relative inability of human macrophages to produce endogenous NO upon external stimulation, they appear to respond to exogenous sources of NO in much the same way as those from other species.…”
Section: Regulation Of Inflammatory Cell Apoptosis By No Myelomonocytmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been demonstrated that, whereas murine-and bovine-stimulated macrophages can produce copious amounts of NO, human, caprine, lapine and porcine cells may not be able to do so. 19,20 Thus, although it is clear that stimulation of murine macrophages with LPS and IFN-g provokes NO production from iNOS, which is sufficient to induce apoptosis, [21][22][23][24] it is by no means certain that this is also the case in human cells. Nevertheless, despite the relative inability of human macrophages to produce endogenous NO upon external stimulation, they appear to respond to exogenous sources of NO in much the same way as those from other species.…”
Section: Regulation Of Inflammatory Cell Apoptosis By No Myelomonocytmentioning
confidence: 99%
“…25 Therefore, observations using NO donors in murine cells could still be extrapolated to human cells, and may provide useful guidance on the potential therapeutic benefits of using NO in inflammatory conditions. Several NO donors have been demonstrated to elicit apoptosis in RAW 264.7 cells, including sodium nitroprusside (SNP), 26 Snitroso-N-acetylpenicillamine (SNAP), [26][27][28] and the NONOates SPER/NO, 21,22,26,27,29 DEA/NO and DETA/NO. 26 In addition, Sandoval et al 30 demonstrated increased apoptosis in RAW 264.7 cells upon exposure to peroxynitrite (ONOO À ; 100-300 mM over 4 h and 10-100 mM over 14 h).…”
Section: Regulation Of Inflammatory Cell Apoptosis By No Myelomonocytmentioning
confidence: 99%
See 3 more Smart Citations